Hybrid PRNG Based On Logistic Map - Tuncer, Taner; Celik, Vedat (Ieee, 2013)
Very well know discrete time chaotic random number generator used in cryptographic applications is Logistic Map. In this paper, we present the implementation of hybrid random number generator based on Logistic Map on Field Programmable Gate Arrays (FPGA). The numbers generated by the hybrid system have been obtained at 32 bit floating point notation. For the usage of cryptographic applications of obtained numbers, these values have been normalized to 0 and 1. Total 20000 numbers have been generated by hybrid system, and they have been tested according to NIST(National Institute of Standarts and Technology) test suite. According to the test result of the numbers obtained from hybrid system, it has been shown that can be used in cryptography applications.
Lojistik harita tabanli hibrit PRNG
21st Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2013 -- CYPRUS
Keywords: Logistic Map; Shrinking Generator; Chaotic Pseudo Random Number Generator